Interpretation of Root Canal Anatomy of Maxillary and Mandibular Permanent Canines in Saudi Subpopulation: A Cone-Beam Computed Tomography (CBCT) Study - Amal A. Almohaimede; Alanoud A. Alqahtani; Norah M. Alhatlani; Nouf S. Alsaloom; Shafia A. Alqahtani (Hindawi Limited, 2021)
The objective of this investigation was to evaluate the root canal anatomy of permanent canines in a Saudi subpopulation utilizing CBCT. A total of 1328 CBCT images of maxillary (634) and mandibular (694) permanent canines were collected from Saudi patients who visited the College of Dentistry at King Saud University in Riyadh. The images were analyzed for root and canal numbers, canal configuration types, and symmetry between the bilateral canine teeth in each arch. Gender, age, and tooth position were recorded. The Kappa test was used for both inter- and intraexaminer reliabilities. Data were analyzed with the chi-square test at a P value≤0.05. There were no two-rooted teeth in maxillary canines, and 1.89% had two canals. Double roots and double canals in mandibular canines were found in 2.88% and 9.94% of the teeth, respectively. Type I canal configuration was more common in maxillary canines (97.94%) compared to mandibular canines (92.07%). Maxillary canines showed higher bilateral symmetries of root and canal numbers and canal configuration types (100%, 98.1%, and 97.9%, resp.) compared to mandibular canines (97.1%, 90.1%, and 92.1%, respectively). The majority of maxillary and mandibular canines had a single root with a single canal and type I canal configuration. Mandibular canines are characterized by having more than one root and canal and alterations in root canal configurations compared to maxillary canines.